Research on Moving Target Detection and Tracking Technology in Sports Video Based on SIFT Algorithm - Zhu Mei; Yue Wang (Advances in Multimedia)
Sports video moving target detection and tracking play an important role in enhancing the popularity of sports and the promotion of sports events. This paper combines the SIFT algorithm to carry out the research of sports video moving target detection and tracking technology, to identify sports features, and to improve the sports feature detection algorithm. Moreover, this paper divides the point cloud data into multiple cube grids under the coordinate system where it is located, and then finds the center of gravity of the data points in each grid, and replaces the coordinates of all points in the grid with the coordinates of the center of gravity. In addition, this paper combines data analysis to verify the algorithm and build a sports video moving target detection system. The experimental research results verify that the sports video target detection and tracking technology based on the SIFT algorithm proposed in this paper has good results.